Three-bladed horizontal axis water turbine simulations with free surface effects (2021)
The water level above a hydrokinetic turbine is likely to vary throughout the season and even along the day. In this work, the influence of the free surface on the performance of a three bladed horizontal-axis turbine is explored by means of a three-dimensional, transient, two-phase flow computational model implemented in the commercial CFD software ANSYS Fluent 19.0. The k − ω SST Transition turbulence model coupled with the Volume of Fluid (VOF) method is used to track the air-water interface. The rotor diameter is . D 0 8m = . Two operating conditions are analyzed: deep tip immersion (0.55D) and shallow tip immersion (0.19D). Three tip speed ratios are evaluated for each immersion. Simulation results show a good agreement with experimental data reported in the literature, although the computed torque and thrust coefficients are slightly underestimated. Details of the free surface dynamics, the flow past the turbine and the wake near the rotor are also discussed